2010
DOI: 10.1002/jcc.21664
|View full text |Cite
|
Sign up to set email alerts
|

Reliable protein structure refinement using a physical energy function

Abstract: In the past decade, significant progress has been made in protein structure prediction. However, refining models to a level of resolution that is comparable with experimental results and can be used in studies like enzymatic activity still remains a major challenge. We have previously demonstrated that our modular protein-solvent energy function, uniquely involving a potential of mean force description for hydrophobic solvation, works well in protein globular structure prediction and loop modeling. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Consistent with the need to use statistically‐derived knowledge‐based potentials for refining comparative models of protein structures, the accuracy of the physics‐based forcefield—such as those in the form of Eq. —has been suggested to be the primary factor limiting the simulation‐based comparative model refinement .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the need to use statistically‐derived knowledge‐based potentials for refining comparative models of protein structures, the accuracy of the physics‐based forcefield—such as those in the form of Eq. —has been suggested to be the primary factor limiting the simulation‐based comparative model refinement .…”
Section: Resultsmentioning
confidence: 99%
“…16,1921 Although successful examples of MD-based refinement have been reported in the past, 2,11,1926 consistent success appears to be hindered by a combination of insufficient sampling, 11,27,28 force field inaccuracies, 20,29 and an inability to reliably identify refined structures that may be generated during the course of an MD simulation. 11,23,2932 To address these issues, statistical potentials 21,3335 and optimized force fields 20,36,37 have been used as well as effective sampling techniques such as replica-exchange 19,24,25,33 and self-guided Langevin dynamics 38 simulations. In some studies it was possible to generate improved structures by as much as 0.5 Å in root-mean-square deviation (RMSD) in one out of five models, 25,33 but reliable identification of a single refined structure remained difficult.…”
Section: Introductionmentioning
confidence: 99%
“…11,23,2932 To address these issues, statistical potentials 21,3335 and optimized force fields 20,36,37 have been used as well as effective sampling techniques such as replica-exchange 19,24,25,33 and self-guided Langevin dynamics 38 simulations. In some studies it was possible to generate improved structures by as much as 0.5 Å in root-mean-square deviation (RMSD) in one out of five models, 25,33 but reliable identification of a single refined structure remained difficult. Recently, Fan et al 24 have shown that by mimicking the electrostatic effects with chaperone Hamiltonian replica-exchange MD simulation can generate refined structures for 10 out of 15 targets with improvements of more than 1 Å RMSD for the secondary structure elements, but again reliable selection of refined structures without knowledge of the native state remained challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a flexible backbone modeling algorithm was applied [18][19][20] . All these methods have attained some degree of success; however, none has emerged as clearly superior 13,14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have worked on developing force fields [6][7][8][9][10][11][12][13][14][15] , and creating better sampling methods [16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%